Overview of underutilized horticultural crops in North-Eastern region - T, Amrutha; Mohanty, A K; H R, Chikkathimme Gowda; Singha, A K; Bordoloi, R M (Indian Farming, 2024)
The study discusses the rich biodiversity and potential of underutilized horticultural crops in the North-eastern region of India. The region, covering only 7.7% of India's total geographic area, is home to more than 50% of the country's biodiversity, with over 60% of the region's crops being underutilized. The study underscores the importance of these underutilized crops in addressing food security, agrobiodiversity conservation, and a more resilient agricultural system. It also highlights the therapeutic diversity of these crops, their potential for value-addition and postharvest management, and their significance in traditional medicine systems. The significance of these underutilized crops in addressing various health issues and contributing to traditional medicine systems is emphasized, along with their potential for income generation for local farmers and sustainable agricultural practices. Additionally, the study addresses the pivotal role of Krishi Vigyan Kendras (KVKs) in fostering awareness among farmers regarding the importance andconservation of these crops.